Analytical and Numerical Solution for Better Positioning in Mines with Potential Extending Application in Space Mining - Stupar, Danijela Ignjatović; Ogrizović, Vukan; Rošer, Janez; Vižintin, Goran (Minerals (Basel), 2022)
Application of new technologies and operational methodologies in mining sector targets to obtain a beneficial outcome in the long term. Instrumentation and monitoring systems for shafts, underground tunneling, storing faculties, etc. are often automated. Implemented systems provide data of mines state, integrated enhanced protection, and early warning solutions. Navigation and positioning in mines are deemed to be unstable in parts of mining tunnels when the external reference points are very far apart, thus significantly increasing the error of the internal network. This paper demonstrates a simulation of an innovative analytical and numerical solution for better positioning in the mines, yielding to increased accuracy of the control points, while reducing the time needed for performing measurements. Based on real tunnel dimensions, different control network configurations are tested. Statistical analysis of simulated environments and virtual measurements, created by combining various instrumentation, confirms cm-level positioning accuracy. The innovative approach to a mine control network design is based on involving fixed-length bars in the network design, gaining in shorter measurements sessions, but keeping homogeneous accuracy throughout the network. The concept is tested on 27 simulated network configurations, combining network points distribution and measurement accuracy of distances and angles. Obtained results and statistical analysis prove that consistent cm-level accuracy can be expected within the network. Extending the concept to space mining, which is becoming an attractive destination for chasing the rare-earth elements (REEs), this methodology will be a spin-off for space exploration mainly applicable in the Lunar lava tube positioning, which are the most secure place to settle the new human life.